2019
DOI: 10.1155/2019/8275491
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting CO2 Emissions in China’s Construction Industry Based on the Weighted Adaboost-ENN Model and Scenario Analysis

Abstract: As a pillar industry of national economy, China’s construction industry is still facing the status of substantial energy consumption and high CO2 emissions, which is a key field of energy conservation and emission reduction. In CO2 emissions research, it is essential to focus on analyzing the present and future trends of CO2 emissions in China’s construction industry. This article introduces a novel prediction model, in which the weighted algorithm is combined with Elman neural network (ENN) optimized by Adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…When the results obtained are compared in detail, the superiority of the proposed method is presented. Zhou et al [27] used a new model to estimate carbon dioxide emissions in China. The proposed model performed well compared to other models, showing the accuracy of the CO 2 emission estimation and the potential for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…When the results obtained are compared in detail, the superiority of the proposed method is presented. Zhou et al [27] used a new model to estimate carbon dioxide emissions in China. The proposed model performed well compared to other models, showing the accuracy of the CO 2 emission estimation and the potential for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer references can be found on Support Vector Machines ( Sun and Liu, 2016 ; Saleh et al., 2016 ; Ahmadi et al., 2019 ) or Regressions ( Köne and Büke, 2010 ; Azadeh et al., 2017 ; Hosseini et al., 2019 ). Not many studies have been found testing other Machine Learning techniques, especially those based on ensemble methods ( Dietterich, 2000 ) like Random Forest ( Wei et al., 2018 ), Adaboost ( Zhou et al., 2019 ) or voting of Multi-layer Perception Classifiers ( Khan and Awasthi, 2019 ).…”
Section: Introductionmentioning
confidence: 99%